Medical Students' Participation in Social Studying and Learning during COVID-19 - Benjamin J. Mead; Suzanne Estaphan; Gerry Corrigan (MDPI AG, 2023)
COVID-19 transformed the medical school learning environment. How social studying and learning (SSL) may have changed was considered worthy of exploration. This study describes the effect of the learning environment transformation on how SSL is conducted by medical students and the reasoning behind any changes. A post-positivist stance was adopted with a mixed method convergent-parallel approach. An online survey explored the participation rate and nature of SSL and how these related to literature-identified underpinning factors that influence participation in SSL. A follow-up interview explored the survey responses. A total of 87 survey responses were collected. Following exclusion of incomplete responses, 57 responses were analysed, and nine follow-up interviews were conducted. Cross-tabulation and logistic regression were conducted to analyse the quantitative data and thematic analysis was conducted to analyse the qualitative data. No significant difference was observed in SSL participation rate during COVID-19. Students transitioned from in-person to Zoom meetings for sensibility, ease and convenience. Students continued participating in SSL for motivation and began participating for accountability, focus and replacement of lost social interaction. The same content was studied using a wider range of activities. Significant decreases were observed in students' perception of the effect of a range of factors. The observed changes to SSL during online learning suggest that SSL is integral for many medical students and will be adapted as required. Given that medical school will always involve some periods of online learning, understanding of the nature of and driving factors behind how medical students engage in SSL during online learning may enable medical educators to support all aspects of student learning.